COMPARISON OF SUSTAINABLE PUBLIC TRANSPORT POLICIES (AN SPECIFIC OPINION OF URBAN POLICY AND PUBLIC INFRASTRUCTURE MANAGEMENT) - Wastam Wastam; Ali Rokhman; Denok Kurniasih (IJOSPOL - International Journal of Social, Policy and Law, 2026)
This study comparatively examines sustainable public transportation policies in Indonesia, Japan, and Germany by focusing on four key dimensions: governance, financing, infrastructure and service quality, and sustainability outcomes. The findings indicate that the effectiveness of sustainable public transportation systems is strongly influenced by institutional capacity, long-term financing mechanisms, integrated infrastructure, and policy commitment to environmental sustainability. Indonesia has made significant progress through the development of mass transit systems such as MRT, LRT, and BRT. However, policy implementation remains constrained by fragmented governance, limited intermodal integration, insufficient financing diversification, and continued dependence on private vehicles. In contrast, Japan has established an integrated transportation system supported by strong public–private partnerships, transit-oriented development (TOD), and efficient rail-based mobility, enabling high service quality and operational sustainability. Germany demonstrates a comprehensive approach through the implementation of Sustainable Urban Mobility Plans (SUMPs), the Verkehrswende agenda, and innovative fare policies such as the Deutschlandticket, which have enhanced accessibility while contributing to emissions reduction and social equity. Comparative analysis reveals that Japan and Germany prioritize system integration, user-oriented services, and measurable sustainability indicators, whereas Indonesia remains primarily focused on infrastructure expansion. The study further emphasizes that successful policy transfer requires adaptation to each country's institutional, fiscal, and socio-demographic contexts rather than direct replication of best practices. Overall, the research concludes that Indonesia needs to shift its policy orientation from infrastructure-centered development toward a sustainable transport system that strengthens institutional coordination, diversifies long-term financing sources, improves service integration and quality, and incorporates environmental performance indicators. Such a transition is essential for achieving an efficient, inclusive, and environmentally sustainable public transportation system capable of supporting long-term urban development and climate objectives.